Monotone Iterative Technique for Nonlinear Impulsive Conformable Fractional Differential Equations With Delay - Thaiprayoon, Chatthai; Ntouyas, Sotiris K.; Tariboon, Jessada (Communications in Mathematics and Applications, 2021)
In this paper, we investigate the existence of solutions for boundary value problems of nonlinear impulsive conformable fractional differential equations with delay. By establishing the associate Green’s function and a comparison result for the linear impulsive problem, we obtain that the lower and upper solutions converge to the extremal solutions via the monotone iterative technique. An example is also presented in the last section.